(untitled) (Rigvedic Himalaya, 2025)
According to ancient principles of Sanatana(eternal) dharma, the four Purusharthas include Dharma (righteous), Artha(just means for acquiring wealth), Kama (fulfilling basic desires and needs of human life), and Moksha i.e enlightenment, be one with the Paramatma. The ultimate goal for human birth is described as Moksha or being one with Paramatma in Adi Shankaracharya’s VivekaChudamani. One needs to go through each Purusharthas in a dharmic way to achieve moksha. The Manu Smriti proclaims that the fundamental foundation of Dharma is Veda. वेदोऽखिलो धर्ममूलं स्मृतिशीले च तद्विदाम् । vedo’khilo dharmamūlaṃ smṛtiśīle ca tadvidām | -Verse 2.6 Manusmriti. It can also be inferred that the attainment of other three modes of Purushartha also emanated from the Veda. Veda as a source is reinforced in Brahma Sutra by sage Badarayana in this Sutra शास्त्रयोनित्वात् ॥ १.१.३॥śāstrayonitvāt. Which states that Paramatma or ParaBrahma can be known only through Vedas. For the ease of consumption Veda is categorized by Sage Veda Vyasa into four parts Rigveda, Yajur Veda, Sama Veda and Atharva Veda. Each of these Veda has an end part called Upanishad. There are 10 principal Upanishads and 108 main Upanishads Along with Veda, there are six ancient texts called darshanas or schools of thought. One such preeminent darshana is Maharishi Patanjali’s Yoga Sutra. This study extracts and provides a vision of underlying connection across Rigveda, Mandukya Upanishad and Yoga Sutra to seek Paramatma. The Mandukya Upanishad having only twelve verses, represents the quintessence of the entire Upanishadic teaching. It analyzes the whole spectrum of human consciousness through the three states of waking (Jagrat), dream (Svapna), and dreamless sleep (Susupti). This Upanishad provides a great symbol for the meditation and the realization of the supreme reality, a mono-syllable AUM. It is considered as “the word of all words”, with three sounds -A, U, M- each one is a representation of the divine entity i.e., deva, Vaisvanara, Taijasa and Prajna respectively. Each of these deities are visualized by Rig Vedic sages, in some instances with the same name as described in Mandukya Upanishad, in other times in derived forms based on the traits associated with each syllable of AUM. In order to contemplate and meditate on this symbol and realize the truth, one needs strong physical and mental health. Sage Patanjali in his pioneering work in Yoga Sutras has indicated the systematic paths in four padas - Samadhi Pada, Sadhana Pada, Vibhuti Pada and Kaivalya Pada. īśvarapraṇidhānādvā -Yoga Sutra 1.23, tasya vācakaḥ praṇavaḥ - Yoga Sutra 1.27. These sutras in the Samadhi pada signify that surrender to īśvara with the sacred word is Om. The Rigveda describes īśvara and its various forms, while the Mandukya upanishad describes praṇavaḥ (Aum) and how to achieve spiritual growth through its contemplation. This paper highlights interconnectivity of these ancient texts which were not explored or studied in detail. In this study, our approach to spiritual growth unearthed a practical guideline for spiritual seekers, drawing from the rich traditions of Vedic philosophy, meditation, and yoga practice, where the seekers can find a structured path toward spiritual enlightenment.